(3OjhGf CHj GdaQL eMeO Hf CMeO GdZSGfj GdTgjQ HGdhGhGA GdOeTbjs - (3GdZSGfj GdOeTbqj, CHh GdaQL, GdhGAhGA, eMeO Hf CMeO, J (B385 (3g`s ((3eMeO Hf WGgQ GdSeGhjs)
(3ChdgG (B:s
(3hegaga cGdZUf gRJg GdUHG aUHG Edjg ef GdbdhH ghGFj (B**s
(3BNQgG (B:s
... (3hbGd (B: (3CjG ef QCi Cf MHj dg PfhHG heG MSfGJj ShGg (B** (3CfgL ef djS jghj ShGc hjghj ghGc hdG Jghg MfGg (B...(3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\213s
(3gOjI GdYGQajf (B2\56s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs